2020
DOI: 10.1016/j.cortex.2020.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Tic frequency and behavioural measures of cognitive control are improved in individuals with Tourette syndrome by aerobic exercise training

Abstract: Previous observations of improvements in cognition in typically developing children following moderate to vigorous exercise (e.g. Budde, Voelcker-Rehage, Pietrabyk-Kendziorra, Ribeiro, and Tidow, 2008;Hillman et al., 2009) have led to increased interest in the potential benefits of exercise for children with neurodevelopmental disorders, involving difficulties in selfregulation (e.g. Halperin and Healy, 2011;Archer and Kostrzewa, 2012). Using a withinsample design, the current study looked at the beneficial ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(73 reference statements)
0
8
0
Order By: Relevance
“…Jackson et al . propose that aerobic exercise training (kick boxing) decreased tic frequency in young people with TS (n = 18, age 10-20 years), likely through enhancement of cognitive control ( Jackson et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Jackson et al . propose that aerobic exercise training (kick boxing) decreased tic frequency in young people with TS (n = 18, age 10-20 years), likely through enhancement of cognitive control ( Jackson et al . 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Physical exercise is advocated as positive for a plethora of somatic and mental disorders these days, and TS is no exception. Jackson et al propose that aerobic exercise training (kick boxing) decreased tic frequency in young people with TS (n = 18, age 10-20 years), likely through enhancement of cognitive control (Jackson et al 2020). Interestingly, tic frequency reduction was less in a Tai Chi group, in which cognitive control enhancement was not significantly altered compared to controls.…”
Section: Other Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several studies have shown that tic frequency can be influenced by antecedent environmental events and social consequences although they referred relatively immediate and short term reaction. For example, some activities reduce tic frequency such as focusing attention away from tics (60), aerobic exercise training (61) and participation in musical activity (62) .There are no reports of an association between maternal psychiatric symptoms and the course of children's tics. However, some studies have shown an association between maternal psychiatric symptoms and the course of children's psychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies have shown that tic frequency can be influenced by antecedent environmental events and social consequences although they referred relatively immediate and short term reaction. For example, some activities reduce tic frequency such as focusing attention away from tics ( 60 ), aerobic exercise training ( 61 ) and participation in musical activity ( 62 ). There are no reports of an association between maternal psychiatric symptoms and the course of children's tics.…”
Section: Discussionmentioning
confidence: 99%